A crítica de Hegel ao conceito de lei em Kant (Revista Eletrônica Estudos Hegelianos, 2016)
RESUMO: Hegel foi um leitor atento da filosofia kantiana, em particular, pela sua pertinência histórica e densidade conceitual. A centralidade da figura do sujeito reúne Kant e Hegel no que diz respeito à determinação da realidade, mas eles se separam na medida em que o sujeito kantiano reconhece o objeto e, diferentemente de Hegel, não se reconhece aí. Tal separação é explorada por Hegel, em sua análise do conceito de liberdade em Kant. Para Hegel, a liberdade em Kant não vai além de uma abstração, enquanto não se deixa determinar. O mesmo raciocínio se estende à lei, pois Hegel entende que Kant opera uma distinção entre a forma e o conteúdo da lei, que não são entendidos como complementares. Em Hegel, a lei é mais do que uma referência formal. Sem a lei, enquanto determinação histórica, a liberdade permanece uma intenção sem jamais atingir o status necessário de realidade entre os homens. Palavras-chave: Legalidade, Efetividade, Comprometimento ABSTRACT: Hegel builds up his philosophical system through an accurate reading of the history of philosophy. In this way it can be said that Hegel was a special Kant’s reader. Kant struck Hegel because of his historical importance and his conceptual depth. Kant and Hegel are brought together insofar they consider the subject and his centrality in relation to the posing of reality. However they also get apart here from one another for in Kant the subject reckons the object but it does not reckon itself in the object like in Hegel. Such a separation is explored by Hegel in his analyses of Kant’s concept of freedom. According to Hegel freedom in Kant remains an abstraction while no determination is achieved. The same thinking is applied to the consideration of law. There is in Kant, so Hegel understands a distinction between the form and the content of law. Form and content are not treated in Kant as complementary. For Hegel law is not only a formal reference but also a necessary determination. Without the law freedom does not go beyond the level of an intention. Freedom is only real in the relationships that men establish among themselves. Keywords: Legality, Effectiveness, Commitment